Production of biochar and activated carbon from oil palm biomass: current status, prospects, and challenges - Zakaria, Mohd Rafein; Ahmad Farid, Mohammad Abdillah; Andou, Yoshito; Ramli, Irmawati; Hassan, Mohd Ali (Elsevier, 2023)
The palm oil industry produces large quantities of biomass residues that can be utilized to produce value-added products. Oil palm biomass has an average carbon content ranging from 42.7 to 57.9, with 3.5–27 fixed carbon, making it a promising source of carbonaceous, thermogenic materials. With estimated yearly production hovering around giga-tonnes, rising interest in bio-based carbonaceous products paves the way for new commercial and scientific applications and holds the potential to be worth millions of dollars on the market as society begins to take the climate crisis gravely. Pyrolysis is the most used technique for converting lignocellulosic feedstock into carbon and energy-rich by-products, with the resulting properties being highly dependent on the feedstock and reaction conditions. This process, which occurs at high temperatures in an oxygen-free or low- oxygen environment, improves carbon content, energy density, surface functionality, and porosity. However, given the lack of a precise technical definition for carbon materials and methods available, studies of biochar and activated carbon (AC) are progressively colliding with one another. Therefore, based on their respective backgrounds and methods of synthesis, their differences are outlined in this report. The present review highlights recent progress and development of biochar and AC from oil palm biomass by looking at the technical aspects of product generation and potential applications. Considering the potential use of these biomass materials for in- house and future applications, strategies, challenges and action should be taken by all parties including government, academia, industry, and consumer to foster the sustainability and circular bioeconomy in the oil palm industry.